Associations between protein to non-protein ratio and intakes of other dietary components in a cohort aged 65-75 years: the Nutrition for Healthy Living Study - Rebecca Luong; Rosilene V Ribeiro; Vasant Hirani; Stephen J Simpson; David G Le Couteur; David Raubenheimer; Alison K Gosby (Cambridge University Press, 2023)
Abstract Objective: Diets with a low proportion of energy from protein have shown to cause overconsumption of non-protein energy, known as Protein Leverage. Older adults are susceptible to nutritional inadequacy. The aim was to investigate associations between protein to non-protein ratio (P:NP) and intakes of dietary components and assess the nutritional adequacy of individuals aged 65-75 years from the Nutrition for Healthy Living (NHL) Study. Design: Cross-sectional. Nutritional intakes from seven-day weighed food records were compared with the Nutrient Reference Values for Australia and New Zealand, Australian Guide to Healthy Eating, Australian Dietary Guidelines and World Health Organisation Free Sugar Guidelines. Associations between P:NP and intakes of dietary components were assessed through linear regression analyses. Setting: NHL Study. Participants: 113 participants. Results: Eighty-eight (59 female and 29 male) with plausible dietary data had a median (interquartile range) age of 69 years (67-71), high education level (86 %) and sources of income apart from the age pension (81 %). Substantial proportions had intakes below recommendations for dairy and alternatives (89 %), wholegrain (89 %) and simultaneously exceeded recommendations for discretionary foods (100 %) and saturated fat (92 %). In adjusted analyses, P:NP (per 1 % increment) was associated with lower intakes of energy, saturated fat, free sugar and discretionary foods and higher intakes of vitamin B12, Zn, meat and alternatives, red meat, poultry and wholegrain % (all P < 0·05). Conclusions: Higher P:NP was associated with lower intakes of energy, saturated fat, free sugar and discretionary. Our study revealed substantial nutritional inadequacy in this group of higher socio-economic individuals aged 65-75 years.